The development of a communication skills training intervention for healthcare professionals caring for people with dementia in the acute hospital setting: an applied conversation analytic study - O'Brien, Rebecca (2019)
A quarter of acute hospital beds are occupied by people with dementia. Concerns have been raised by government and carers about the quality of communication between staff and those with dementia in hospital in the UK. People with dementia may experience communication impairments such as word finding difficulties, repetitive utterances, lack of coherent speech narratives and difficulties understanding the speech of others. Since much healthcare delivery occurs through ‘talk’, healthcare professionals and hospital patients with dementia are likely to experience increased communication barriers. Consistent with this, healthcare professionals report stress and reduced job satisfaction associated with difficulty communicating with their patients with dementia.